Some gold, a little ivory: country tales form Ghana and the ivory coast - Haskett, Edythe Rance (New York: John Day Company, 1971)
Twenty-four folk tales that reflect the history, legends, and ethics of the people of Ghana and the Ivory Coast.
Keywords: Tales -- Africa, West